2021
DOI: 10.1016/j.ces.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HCl and steam on cyclic CO2 capture performance in calcium looping systems

Abstract: The effect of HCl and steam addition during carbonation and calcination using a Canadian limestone was investigated.  The experiments were conducted using thermogravimetric analysis and fixed bed reactor testing.  The presence of HCl was found to increase sorbent reactivity towards CO 2 capture when steam was injected during calcination.  Full sorbent dechlorination can be expected under typical oxy-fuel calcination conditions.  The decomposition of CaCl 2 to CaO during calcination caused changes in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Daoudi et al [44] conducted thermogravimetric studies and reported that the conversion of CaO was increased from 70% to 90% in the presence of HCl. Studies by Symonds et al with steam as the feeding gas have also confirmed that adding HCl to the carbonation step results in simultaneous carbonation and chlorination of CaO and their corresponding products are CaCO3, CaCl2, and CaClOH [24]. These findings support the hypothesis that the formation of chlorination products on the surface of the CaO particles is beneficial.…”
Section: Co 2 Capture Efficiency Through Carbonation-calcination Loopingsupporting
confidence: 58%
See 1 more Smart Citation
“…Daoudi et al [44] conducted thermogravimetric studies and reported that the conversion of CaO was increased from 70% to 90% in the presence of HCl. Studies by Symonds et al with steam as the feeding gas have also confirmed that adding HCl to the carbonation step results in simultaneous carbonation and chlorination of CaO and their corresponding products are CaCO3, CaCl2, and CaClOH [24]. These findings support the hypothesis that the formation of chlorination products on the surface of the CaO particles is beneficial.…”
Section: Co 2 Capture Efficiency Through Carbonation-calcination Loopingsupporting
confidence: 58%
“…Many studies have demonstrated that the reactivity and recyclability of the calciumbased sorbent are crucial factors in the economic viability of the CaL [19]. Most of Cabased materials exhibit continuous deactivation in presence of gaseous contaminants and cyclic operation [20][21][22][23][24]. In addition, attrition is another issue for natural calcium material such as limestone.…”
Section: Introductionmentioning
confidence: 99%
“…The HCl addition in the previous three cycles demonstrated the highest initial carbonation conversion and the most stable amongst other cycles at a calcination temperature of 850 °C. However, the result contradicts the study by Symnonds et al(2021) [ 132 ] where HCl demonstrated low carbonation conversion at 870 °C due to the formation of calcium chloride (CaCl 2 ) onto the surface, causing an increase in CO 2 diffusion resistance. Moreover, the contradiction is probably due to the number of HCl additions during the carbonation stages.…”
Section: Improvement Of Sorbentmentioning
confidence: 62%
“…Based on previous testing, where CaO carbonation profiles were compared at multiple flowrates ranging from 50-200 NmL/min, it has been shown that the selected operating conditions limit gas diffusion resistance from the bulk gas to the particle surface. [10,11] In addition, Perejon et al [12] performed similar testing using a gas flow rate of 50 mL/min and noted that gas diffusion resistance through the sample only becomes relevant for sample masses above 40 mg for their TGA setup.…”
Section: Experimental Methodsmentioning
confidence: 99%